Hypermethylation of mitochondrial transcription factor A induced by cigarette smoke is associated with chronic obstructive pulmonary disease. (21st April 2019) - Peng, Hong; Guo, Ting; Chen, Zhiyong; Zhang, Hongliang; Cai, Shan; Yang, Min; Chen, Ping; Guan, Chaxiang; Fang, Xiang
Abstract: Purpose of the study: Cigarette smoking is a leading environmental contributor to chronic obstructive pulmonary disease (COPD), but its epigenetic regulation of mtTFA gene remains elusive. This study aims to explore the relationship of DNA methylation of mtTFA and cigarette smoking in COPD. Materials and Methods: We analyzed DNA methylation on mtTFA promoters in clinical samples from COPD patients and subjects with normal pulmonary function. Expression of mtTFA mRNA in the clinical samples and mtTFA mRNA and protein in human umbilical vein endothelial cells(HUVECs) treated with cigarette smoke extract (CSE) was evaluated. mtTFA mRNA and protein levels were measured to determine effects of demethylation agents on CSE-treated HUVECs. Results: The DNA methylation level of the mtTFA promoter was significantly increased in COPD group. Expression of mtTFA mRNA was downregulated in the lungs as a consequence of hypermethylation of mtTFA promoter. Expression of mtTFA mRNA and protein was downregulated in CSE-treated HUVECs as a consequence of hypermethylation of the mtTFA promoter. mtTFA expression in CSE-treated HUVECs was restored by the methylation inhibitor, 5-aza-2'-deoxycytidine(AZA). Conclusions: Cigarette smoke-induced hypermethylation of the mtTFA promoter is related to the initiation and progression of COPD. Our finding may provide a new strategy for the intervention of COPD by developing demethylation agents targeting mtTFA hypermethylation.